2021
DOI: 10.3390/microorganisms9102117
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A, an Active Liaison for Host-Microbiota Homeostasis

Abstract: Mucosal surfaces in the gastrointestinal tract are continually exposed to native, commensal antigens and susceptible to foreign, infectious antigens. Immunoglobulin A (IgA) provides dual humoral responses that create a symbiotic environment for the resident gut microbiota and prevent the invasion of enteric pathogens. This review features recent immunological and microbial studies that elucidate the underlying IgA and microbiota-dependent mechanisms for mutualism at physiological conditions. IgA derailment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 282 publications
(365 reference statements)
0
15
0
2
Order By: Relevance
“…We also investigated B-cell levels in the spleen and bone marrow because circulating IgA is primarily secreted by mature plasma cells in the bone marrow. 4,18 The % CD45RA + total B-cell population in circulation and Peyer patches were significantly lower in SHR compared to WKY rats (Figure 4A and 4B). In addition, the % CD45RA + CD127 + immature B-cell subset in SHR was substantially reduced in circulation, Peyer patches, and spleen but not in bone marrow (Figure 4C and 4D, Figure S6A and S7A), implicating that SHR has no defect in B cell development in the bone marrow.…”
Section: Shr Have Diminished B Cells In Circulation and Peyer Patchesmentioning
confidence: 94%
“…We also investigated B-cell levels in the spleen and bone marrow because circulating IgA is primarily secreted by mature plasma cells in the bone marrow. 4,18 The % CD45RA + total B-cell population in circulation and Peyer patches were significantly lower in SHR compared to WKY rats (Figure 4A and 4B). In addition, the % CD45RA + CD127 + immature B-cell subset in SHR was substantially reduced in circulation, Peyer patches, and spleen but not in bone marrow (Figure 4C and 4D, Figure S6A and S7A), implicating that SHR has no defect in B cell development in the bone marrow.…”
Section: Shr Have Diminished B Cells In Circulation and Peyer Patchesmentioning
confidence: 94%
“…Furthermore, BAFF favors the survival of high-affinity B-cell clones and activates class switch recombination of immunoglobulins [ 34 , 35 ]. It has been demonstrated that overexpression of BAFF in mice induces a significant expansion of activated B-cells and marginal zone B-cells, as well as hypergammaglobulinemia and autoantibody production [ 36 , 37 ]. On the other hand, BAFF co-stimulates T-cell activation and proliferation and promotes its differentiation into effector cells [ 38 ].…”
Section: Baff Biology and Role In Other Diseasesmentioning
confidence: 99%
“…Activation of B cells leads to the secretion of IgA, which plays an important role in the regulation of the gut microbiome. Immunoglobulin A, on the one hand, is involved in the binding and elimination of pathogenic bacteria, and on the other hand, it facilitates the translocation of commensals into Peyer's patches, activating the mechanisms of immunological tolerance and thereby stimulating the growth of intestinal symbionts[ 30 , 31 ].…”
Section: Gut Microbiota and Intestinal Barriermentioning
confidence: 99%